Matrix acidizing with gelled acid - Ismail, Issham; Kweh, Wei Loon (Penerbit UTM Press, 2003)
A laboratory investigation was conducted to compare the efficiency of gelled acid with conventional/plain mud acid in removing the formation damage induced by water-based mud. An acidizing system was developed to study the effect of flow/injection rate and gel viscosity on Berea sandstone. The main equi pments used in this research study were stainless steel core holder, mud cells, valves, and 3 mm tubing. The treatment fluids used were mud acid (3% HF–12% HCl), hydrochloric acid, and polymer gel (xanthan gum). The experimental results revealed that polymer gel with viscosity lower than 73 cP gave better performance as compared to polymer gel with viscosity greater than 73 cP. At gel viscosity of 73 cP, the permeability ratio was 3.5 compared to 1.5 only at viscosity of 126 cP. This was due to the permanent plugging by the high viscosity polymer gel in the core after the injection. Gelled acid has shown tremendous improvement in removing formation damage, where polymer gel with viscosity of 73 cP was found to give better treatment at flow rate of 0.28 ml/s as compared to lower flow rates.